2022
DOI: 10.12998/wjcc.v10.i4.1172
|View full text |Cite
|
Sign up to set email alerts
|

Sequential sagittal alignment changes in the cervical spine after occipitocervical fusion

Abstract: BACKGROUND There are few studies regarding sequential changes in the sagittal alignment of the upper and lower cervical regions of the spine after occipitocervical fusion (OCF). In addition, no comparisons of cervical sagittal alignment (CSA) between patients with craniocervical junction disorders (CJDs) and normal populations have been reported. AIM To compare the CSA of patients with CJDs with that of normal controls and investigate the sequential changes in the CSA o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…As life expectancy increases worldwide, degenerative diseases of the lumbosacral spine are becoming more common[ 1 ]. Debilitating conditions are currently the major causes of morbidity, disability, and lost productivity[ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…As life expectancy increases worldwide, degenerative diseases of the lumbosacral spine are becoming more common[ 1 ]. Debilitating conditions are currently the major causes of morbidity, disability, and lost productivity[ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The explanation is that as the C0-C2 angle decreases, the cranium's center of gravity shifts forward, requiring the lower spine's lordosis (CL) to drop to maintain the horizontal gaze. 21 However, the (C0-C2)-C2S mismatch between the revision and nonrevision surgery groups is a discovery that is new to us, and we do not yet have a good explanation. However, we concur with other authors 23 , 26 that alterations at C0-C2 and CL are a physiologic mechanism for maintaining horizontal gaze in response to thoracolumbar malalignment.…”
Section: Discussionmentioning
confidence: 97%
“…However, no notable differences in C0-C2 angle or C2S were found between the revision and nonrevision groups. Studies 20 , 21 have suggested that the normal value of C0-C2 angle should be in the range of 0 0 to 30 0 , in health individual, and more than 30 0 was reported to associate with complications such as dysphagia and cervical misalignment. In this study, all patients in revision and nonrevision groups have values of C0-C2 angle within the range of the health individual.…”
Section: Discussionmentioning
confidence: 99%